Reckless - Funke, Cornelia; Wigram, Lionel; Latsch, Oliver (New York : Little, Brown, 2010)
Jacob and Will Reckless have looked out for each other ever since their father disappeared, but when Jacob discovers a magical mirror that transports him to a warring world populated by witches, giants, and ogres, he keeps it to himself until Will follows him one day, with dire consequences.
Translated from the German.
Keywords: Fantasy; Brothers -- Fiction; Adventure and adventurers -- Fiction; Magic -- Fiction; Fantasy fiction; Brothers -- Juvenile fiction; Adventure stories; Magic -- Juvenile fiction